Association between polyunsaturated fatty acids intake and serum neurofilament light chain concentrations in American adults: a cross-sectional study - Wang, Yuxuan; Wang, Jingyi; Wang, Lifeng (Frontiers in Nutrition, 2025)
BackgroundSerum neurofilament light chain (sNfL) is a promising blood-based biomarker for detecting neuroaxonal injury, with elevated levels observed in various neurological disorders. While polyunsaturated fatty acids (PUFAs) have been linked to favorable neurological outcomes, the relationship between dietary PUFAs intake and sNfL levels remains unclear. This study aimed to investigate the association between PUFAs intake and sNfL levels in American adults.MethodsA cross-sectional study was conducted using data from the National Health and Nutrition Examination Survey (NHANES) 2013–2014. Multivariable regression analyses were applied to examine the associations between individual PUFA, omega-3 PUFAs, omega-6 PUFAs, and omega-6/omega-3 ratio and sNfL levels. Restricted cubic spline (RCS) models were used to assess potential non-linear relationships. The overall effect of PUFAs mixtures on sNfL was assessed using quantile g-computation (QGC), while weighted quantile sum (WQS) regression was applied for sensitivity analysis.ResultsA total of 1,109 eligible participants were included in the study. Alpha-linolenic acid (ALA), linoleic acid (LA), docosahexaenoic acid (DHA), docosapentaenoic acid (DPA), and eicosapentaenoic acid (EPA) were inversely associated with sNfL levels after adjusting for all covariates. Omega-3 and omega-6 PUFAs were negatively associated with sNfL, whereas the omega-6/omega-3 ratio was positively associated with sNfL. Findings from WQS and QGC analyses further supported an inverse association between PUFA mixtures and sNfL levels.ConclusionThis study indicates that PUFAs intake is associated with decreased levels of sNfL, suggesting a potential association with reduced neuroaxonal injury. Further studies are needed to validate these findings and explore the biological pathways.